Uma Análise verbal do discurso do comportamento verbal de acompanhantes terapeuticos. - Fernanda Gomes de Souza (2023)
This experiment is based on the premise established by radical Behaviorism, as a philosophy that underpins the science of Behavior Analysis, with behavior being the object of study of this epistemology. Given this assumption, the object of study of the research is the explanatory discourse of therapeutic companions about children's behavior, specifically therapeutic companions who work with neurodivergent people. To carry out the experiment, a discourse analysis was carried out, implementing the Reno Method in verbal discourse about functional analysis situations. The following parameters are investigated: a) evaluate the contingency components that produced verbal behaviors and classify them according to the Reno Method; and b) evaluate the differences and similarities in the explanatory behavior of therapeutic companions Psychologists and therapeutic companions with other training. The research was carried out in two stages, the first of reviewing the bibliography for support, the second of applying the experiment, which in turn is divided into: a) data collection where verbalizations occurred in the face of an antecedent stimulus organized by the researcher, allowing to analyze the sources of control of verbal behavior; and b) self analysis of the scientist's behavior. Ten participants participated in the experiment, 5 of whom were psychologists and 5 of whom were therapists with other training. The interviews were recorded, transcribed and, later, analysis categories were created based on verbalizations. Based on such analyses, comparisons were made between the groups, with both groups issuing verbal responses from the same categories, with variations between categories and response frequencies when faced with antecedent stimuli. The research indirectly contributed to the psychologist's verbal behavior and behavior analysis, the impact of training and the training of professional therapeutic companions. In short, each person's history may imply the frequency of mentalistic responses. Keywords: Verbal behavior. Behavior analysis. Therapeutic companion